RENAL PATHOLOGY IN PATIENTS WITH COVID-19 (World Bulletin of Public Health, 2024)
SARS-CoV-2 virus (COVID-19) is highly contagious, virulent and shows tropism to many human organ cells. To enter the cell, SARS-CoV-2 virus utilizes the angiotensin-converting enzyme type 2 (ACE2) receptor, which is highly expressed in the kidney. Through the ACE2-dependent signaling pathway, SARSCoV-2 can directly infect renal tubule epithelium and podocytes
Keywords: SARS-CoV2; kidneys; endotheliitis